Study on the high-temperature triggering and holding characteristics of PDSOI SCR devices. (November 2021) - Wang, J.X.; Zhao, F.Z.; Ni, T.; Li, D.L.; Gao, L.C.; Wang, J.J.; Li, X.J.; Zeng, C.B.; Luo, J.J.; Han, Z.S.
Abstract: In this paper, the triggering and holding characteristics of electrostatic discharge (ESD) protection devices operating under various ambient temperatures ranging from 25 °C to 300 °C are investigated. The measured ESD protection devices were silicon-controlled rectifier (SCR) devices fabricated in 0.18-μm partially depleted silicon-on-insulator (PDSOI) technology. Measurements were conducted using the transmission line pulse (TLP) test system. The triggering voltage, V T1, and the holding voltage, V H, of the SCR devices show negative coefficient phenomenon with the increasing temperature. The similarities and differences between the triggering condition and the holding condition are analyzed in detail. The underlying physical mechanisms related to the effects of temperature on the V T1 and V H are provided by the assist of technology computer-aided design (TCAD) simulation. Highlights: The high-temperature triggering and holding characteristics of PDSOI SCR devices is investigated The TCAD-based high temperature simulation method is developed and used The mechanism of the high-temperature triggering and holding characteristics is analyzed The risk of high-temperature ESD device application is proposed